UNCITRAL / Legal Guide on Drawing up International Contracts for the Construction of Industrial Works - United Nations (1988)
Foreword, Introduction, Pre-Contract Studies, General Remarks on Drafting, Transfer of Technology, Price and Payment Conditions, Construction on Site, Consulting Engineer, Subcontracting, Passing of Risk, Transfer of Ownership of Property, Insurance, Security for Performance, Damages, Exemption Clauses, Hardship Clauses, Variation Clauses, Suspension of Construction, Termination of Contract, Transfer of Contractual Rights and Obligations, Choice of Law, Settlement of Disputes, Index.